2022
DOI: 10.3390/cells11182828
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Gastric Cancer Stem Cells to Enhance Treatment Response

Abstract: Gastric cancer (GC) was the fourth deadliest cancer in the world in 2020, and about 770,000 people died from GC that year. The death of patients with GC is mainly caused by the metastasis, recurrence, and chemotherapy resistance of GC cells. The cancer stem cell theory defines cancer stem cells (CSCs) as a key factor in the metastasis, recurrence, and chemotherapy resistance of cancer. It considers targeting gastric cancer stem cells (GCSCs) to be an effective method for the treatment of GC. For GCSCs, genes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 181 publications
0
10
0
Order By: Relevance
“…Furthermore, gastric CSCs are involved in metastasis and recurrence in gastric cancer (Becerril-Rico et al, 2021;Yang et al, 2022). Therefore, targeting stemness is rising as a new therapeutic strategy in gastric cancer (Rao et al, 2022). HIF-1α is a key stimulator of stemness in gastric cancer.…”
Section: Hif-1α and Stemness In Gastric Cancermentioning
confidence: 99%
“…Furthermore, gastric CSCs are involved in metastasis and recurrence in gastric cancer (Becerril-Rico et al, 2021;Yang et al, 2022). Therefore, targeting stemness is rising as a new therapeutic strategy in gastric cancer (Rao et al, 2022). HIF-1α is a key stimulator of stemness in gastric cancer.…”
Section: Hif-1α and Stemness In Gastric Cancermentioning
confidence: 99%
“…Several successes achieved in patients with HER2+ BC have not been reproduced in patients with HER2+ GC, mainly owing to several biological differences, including the higher degree of heterogeneity of HER2 expression in GC and the coexistence of other genomic drivers beyond HER2 itself [41]. Since altered HER2 signaling has a central role in the maintenance/survival of breast CSCs [12] and despite the availability of limited data on HER2+ GC stemness [15], the addition of GCSC-targeted therapies to current treatment options may be a key step for improving patient outcomes [6,42]. In this context, we found that the intrinsic sensitivity of the tested HER2+ GC cells to HER2 targeting is positively associated with the per se capability of anti-HER2 agents to impair gastrosphere formation; indeed, only low or no levels of GFE % inhibition were observed in T-resistant cell targets, confirming the existence of additional drivers supporting cancer stemness features.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CSCs are able to continuously self-renew and differentiate into distinct lineages, being deeply implicated in tumor initiation, invasiveness, metastases, treatment resistance and in immune escape [7,8]. Thus, targeting molecular drivers involved in the CSC program, including the dysregulated expression/activation of HER2 and its splice variant d16HER2 in HER2+ breast [9][10][11][12] and gastric [13][14][15] cancers, may improve cancer patient outcomes, yielding long-lasting responses [16].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) remains one of the most incident neoplasms and the third leading cause of cancer-related death [ 1 ].The dysregulation of oncogenic and tumor suppressor genes and pathways result in the stepwise accumulation of numerous epigenetic alterations [ 2 ]. It has been reported that gastric cancer stem cells (GCSCs) function as vital contributors to tumor initiation, progression, metastasis and relapse, drug resistance [ 3 ].GCSCs possess the ability of unlimited self-renewal and heterogeneous differentiation, and they have been described highly resistant to currently available chemotherapy and targeted therapy in GC [ 4 , 5 ]. Therefore, understanding the molecular mechanisms that enhances the stemness of GC cells will provide new strategies to improve GC treatments.…”
Section: Introductionmentioning
confidence: 99%